2011
DOI: 10.1152/advan.00127.2010
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a multimedia e-learning resource for electrolyte and acid-base disorders

Abstract: This article reports on the development and evaluation of a Web-based application that provides instruction and hands-on practice in managing electrolyte and acid-base disorders. Our teaching approach, which focuses on concepts rather than details, encourages quantitative analysis and a logical problem-solving approach. Identifying any dangers to the patient is a vital first step. Concepts such as an "appropriate response" to a given perturbation and the need for electroneutrality in body fluids are used repea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 46 publications
(42 reference statements)
1
33
0
1
Order By: Relevance
“…22 Patient simulation via virtual patient software has been used throughout higher education by multiple disciplines. [23][24][25][26][27][28][29][30] The design, development, implementation, and assessment of a novel approach to integrate the skills and attitudes of SDL into an advanced therapeutics course within a pharmacy curriculum using virtual patient software is described. This teaching strategy combines educational technology with principles of social learning in order to supplant lecture and support learners in exercising autonomy related to the learning endeavor.…”
Section: Introductionmentioning
confidence: 99%
“…22 Patient simulation via virtual patient software has been used throughout higher education by multiple disciplines. [23][24][25][26][27][28][29][30] The design, development, implementation, and assessment of a novel approach to integrate the skills and attitudes of SDL into an advanced therapeutics course within a pharmacy curriculum using virtual patient software is described. This teaching strategy combines educational technology with principles of social learning in order to supplant lecture and support learners in exercising autonomy related to the learning endeavor.…”
Section: Introductionmentioning
confidence: 99%
“…Literature search has demonstrated that researchers have used various forms of E-learning tools such as streaming video, multimedia, and web-based interactive modules. [10][11][12] In pharmacology too, researchers have used E-learning tools to improve prescribing skills, delivering concepts in clinical pharmacology and therapeutics. [13,14] In our study, out of the three ELMs considered, models 1 and 2 represent two different approaches to the blended learning technology since they utilize traditional didactic teaching supplemented with internet resources.…”
Section: Discussionmentioning
confidence: 99%
“…[25] Formal usability evaluation revealed that serious usability problems rendered the resource unusable for many participants. [26] Some researchers have found significant learning effects from optimising the usability of learning materials.…”
Section: Fostering Generative Processingmentioning
confidence: 99%
“…We should therefore consider incorporating instructional design features aimed at priming motivation, while being careful not to overload the learner's working memory. [40] Our own experience [25,26,31,32] has illustrated how clinician-teachers who are not usability Table 2. Principles of good interface design.…”
Section: Fostering Generative Processingmentioning
confidence: 99%
See 1 more Smart Citation